Beroende eller oberoende? En kvalitativ studie av hur äldre hjälptagare ser på att ha hjälp och stöd (Sociologisk Forskning, 2007)
Dependency or independence? A qualitative study of how elderly home-help recipients regard having help and supportKnowledge on elderly people’s understandings of dependence and independence is relatively scarce even though there is plenty of gerontological research on related topics. Although we know how to define and measure different types of dependency, we know, in fact, very little about how elderly home-help recipients themselves regard their situation in terms of dependency, independence and autonomy. This article aims to shed light on home-help recipients’ understandings of these constructs and on how they make sense of their situation. The analysis is based on 29 semi-structured interviews with people between the ages of 77 and 93. The findings show how these home help recipients differentiate between having help and support and being dependent on other people. Through the separation of aspects of these understandings, such as the reason why they accept help and support and how they regard the situation of being helped and assisted, three ways of regarding the situation have been identified, which stress the variability of the social construction of dependency and independence that these elders uphold. Some home-help recipients construct themselves as independent, others as autonomous and able selves, while a third group construct themselves as powerless.
Keywords: elderly; dependency; independence; home-help care recipients